Composition for preparing ABS (Acrylonitrile Butadiene Styrene) rubber powder, ABS rubber powder as well as preparation method and application of ABS rubber powder
By using a composition wrapped in the graft shell in the preparation of ABS resin, the warping deformation and plating peeling problems of ABS resin in the high and low temperature cycle tests were solved, and higher plating binding force and lower linear expansion coefficient were achieved.
Patent Information
- Application Number
- CN202311412373.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-27
- Publication Date
- 2025-04-29
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing ABS resin is prone to warping and deformation, plating/substrate cracking, plating bubbling and plating shedding in high and low temperature cycle tests, and the performance improvement of the physical blending method is unstable.
ABS resin with conductive nanomaterial wrapped in a graft shell was prepared by using a composition of polybutadiene latex, styrene, acrylonitrile and conductive nanomaterials in the preparation of ABS powder.
It significantly improves the surface conductivity and thermal properties of ABS resin, reduces the linear expansion coefficient, enhances the electroplating binding force, and solves the cracking and bulging problems of resin in high-temperature applications.
Smart Images

Figure CN119899322A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to ABS resin, in particular to an ABS resin with low linear expansion coefficient and high electroplating bonding force. Background Art
[0002] As modern cars become increasingly lightweight and people's aesthetic taste for cars improves, electroplated plastics can not only achieve lightweight, but also create a luxurious and beautiful sense of luxury. Plastic electroplating parts have many advantages, such as: metallic luster, excellent electrical and thermal conductivity, solvent resistance, etc. Acrylonitrile-butadiene-styrene (ABS) copolymer is easy to electroplate due to its own molecular structure and phase composition. Currently, more than 90% of electroplated plastic parts on the market are based on ABS or ABS blends as electroplating substrates.
[0003] As market competition continues to intensify, the quality requirements for ABS plastic electroplated parts are getting higher and higher. Usually, each OEM has clear requirements for the bonding strength of the coating on plastic electroplated parts, and also requires that ABS plastic electroplated parts can withstand high and low temperature cycle tests from -40℃ to 80~90℃. Since the linear expansion coefficients of plastic and metal coatings differ by several orders of magnitude, changes in ambient temperature will lead to large differences in the dimensional changes between the electroplating layer and the resin layer, which can easily cause problems such as warping of parts, cracking of the coating / substrate, blistering of the coating, and even large-scale shedding of the coating.
[0004] At present, most of the existing technologies only modify or improve the performance of ABS resin at the blending end. However, the biggest disadvantage of this simple physical blending method is that the performance improvement is unstable and the improvement effect is not very significant, which makes it impossible to solve the above problems. Summary of the invention
[0005] To overcome at least one defect of the above-mentioned prior art, in a first aspect, an embodiment of the present invention provides a composition for preparing ABS rubber powder, comprising polybutadiene latex, styrene, acrylonitrile and additives, wherein the additives include conductive nanomaterials.
[0006] In a second aspect, an embodiment of the present invention provides a method for preparing ABS rubber powder, comprising preparing ABS rubber powder by using the above-mentioned composition; wherein the ABS rubber powder comprises a core layer and a shell layer, and the shell layer comprises a conductive nanomaterial.
[0007] In a third aspect, an embodiment of the present invention provides an ABS rubber powder, comprising a core layer and a shell layer, wherein the shell layer comprises a conductive nanomaterial.
[0008] In a fourth aspect, an embodiment of the present invention provides a composition for preparing ABS resin, comprising the ABS rubber powder prepared by the above preparation method or the above ABS rubber powder and styrene-acrylonitrile copolymer.
[0009] In a fifth aspect, an embodiment of the present invention provides an electroplated product, comprising a substrate layer and an electroplating layer, wherein the substrate layer comprises an ABS resin prepared from the above-mentioned composition.
[0010] A composition for preparing ABS rubber powder according to an embodiment of the present invention comprises a conductive nanomaterial. When the composition is used to prepare ABS rubber powder, the conductive nanomaterial can be wrapped in a graft shell layer of the prepared graft latex, so that not only the surface conductivity of the subsequently prepared resin can be significantly improved, but also the linear expansion coefficient of the resin can be reduced. BRIEF DESCRIPTION OF THE DRAWINGS
[0011] The accompanying drawings are only used to illustrate specific embodiments and are not to be considered as limiting the present invention.
[0012] Figure 1 It is a test curve diagram of electroplating bonding strength of Examples 1-4, Comparative Example 2 and Comparative Example 3 of the present invention;
[0013] Figure 2 TEM image of the ABS resin latex of Comparative Example 3 of the present invention;
[0014] Figure 3 TEM images of the ABS resin latex of Examples 1-4 of the present invention. DETAILED DESCRIPTION
[0015] Typical embodiments that embody the features and advantages of the present invention will be described in detail in the following description. It should be understood that the present invention can have various changes in different embodiments without departing from the scope of the present invention, and the descriptions therein are essentially used as illustrations rather than to limit the present invention.
[0016] An embodiment of the present invention provides a composition for preparing ABS rubber powder, comprising polybutadiene latex, styrene, acrylonitrile and additives, wherein the additives include conductive nanomaterials.
[0017] In one embodiment, the composition for preparing ABS rubber powder includes 40 to 80 parts by mass of polybutadiene latex, 20 to 40 parts by mass of styrene, 5 to 20 parts by mass of acrylonitrile and 0.2 to 6 parts by mass of conductive nanomaterials; further, the amount of conductive nanomaterials can be 0.5 to 6 parts by mass, such as 1 part by mass, 2 parts by mass, 2.5 parts by mass, 3 parts by mass, 3.5 parts by mass, 4 parts by mass, 4.5 parts by mass, and 5 parts by mass. Herein, the amount of polybutadiene latex is calculated based on its cured amount, and 40 to 80 parts by mass of polybutadiene latex means that the solid content in the polybutadiene latex is 40 to 80 parts by mass.
[0018] In one embodiment, the mass content of the conductive nanomaterial in the composition for preparing ABS rubber powder can be 0.1-8.5%, and further can be 0.49-5.7%, for example, 0.15%, 0.2%, 0.25%, 0.3%, 0.5%, 0.9%, 1%, 1.5%, 1.9%, 2%, 2.5%, 2.9%, 3%, 3.5%, 3.85%, 4%, 4.5%, 5%, 5.5%, 5.7%, and 6%.
[0019] In one embodiment, the composition for preparing ABS rubber powder further includes a reaction aid. Further, the reaction aid may include one or more of an activator, an initiator, and a molecular weight regulator; and the additive may include an emulsifier and / or an antioxidant.
[0020] In one embodiment, the composition for preparing ABS rubber powder includes 40 to 80 parts by mass of polybutadiene latex, 20 to 40 parts by mass of styrene, 5 to 20 parts by mass of acrylonitrile, 0.001 to 0.004 parts by mass of activator, 0.002 to 0.2 parts by mass of initiator, 0.1 to 0.6 parts by mass of molecular weight regulator, 0.1 to 0.6 parts by mass of emulsifier, 0.05 to 0.3 parts by mass of antioxidant (e.g., composite liquid antioxidant) and 0.5 to 5 parts by mass of conductive nanomaterial. Further, the amount of initiator can be 0.05 to 0.15 parts by mass, for example, 0.1 parts by mass; the amount of composite liquid antioxidant can be 0.1 to 0.2 parts by mass.
[0021] In one embodiment, the composition for preparing ABS rubber powder includes 60 parts by mass of polybutadiene latex, 30 parts by mass of styrene, 10 parts by mass of acrylonitrile, 0.002 parts by mass of activator, 0.1 parts by mass of initiator, 0.2 parts by mass of molecular weight regulator, 0.3 parts by mass of emulsifier, 0.1 parts by mass of composite liquid antioxidant and 0.5-6 parts by mass of conductive nanomaterial.
[0022] In one embodiment, the particle size of the polybutadiene latex is 100 to 800 nm, and further 200 to 400 nm. Wherein, the polybutadiene latex with the corresponding particle size can be directly obtained in one step by emulsion polymerization; or after obtaining a polybutadiene latex of about 100 nm by emulsion polymerization, the corresponding large-particle latex is obtained by chemical agglomeration. Wherein, the latex particle size is measured using a Malvern Zetasizer NanoZSP particle size analyzer, and the specific test method is: weigh 0.5g of latex, dilute it with 100g of deionized water, weigh 1g of the diluted liquid and dilute it again with 100g of deionized water. Take an appropriate amount of the diluted latex and pour it into a cuvette, and use the Malvern Zetasizer NanoZSP particle size analyzer to test the average particle size.
[0023] In one embodiment, the solid content of the polybutadiene latex is 45-55 wt %, such as 48 wt %, 50 wt %, or 52 wt %.
[0024] In one embodiment, the conductive nanomaterial includes one or more conductive nanoparticles such as graphene, nano-copper, nano-nickel, carbon nanotubes, etc., for example, nano-copper powder and nano-nickel powder.
[0025] In one embodiment, the activator is a ferrous salt, such as ferrous sulfate; the initiator can be a peroxide, such as cumene hydroperoxide; the molecular weight regulator can be a thiol compound, such as tert-dodecyl mercaptan; the emulsifier can be a fatty acid soap, such as potassium oleate; the antioxidant can be a composite emulsion antioxidant, such as FK301 (Shandong Fengquan New Materials Co., Ltd.).
[0026] An embodiment of the present invention provides a method for preparing ABS rubber powder, comprising preparing ABS rubber powder by using the above composition. Further, the prepared ABS rubber powder comprises a core layer and a shell layer structure, and the shell layer contains a conductive nano material.
[0027] In one embodiment, the core layer of the ABS rubber powder includes polybutadiene latex, and the shell layer includes a graft copolymer of acrylonitrile and styrene.
[0028] In one embodiment, the particle size of the ABS latex may be 100 to 1000 nm, for example, 110 nm, 120 nm, 200 nm, 300 nm, 400 nm, 500 nm, 600 nm, 700 nm, 800 nm, and 900 nm.
[0029] In one embodiment, the mass content of the conductive nanomaterial in the ABS rubber powder can be 0.1-8.5%, and further can be 0.49-5.7%, for example, 0.15%, 0.2%, 0.25%, 0.3%, 0.5%, 0.9%, 1%, 1.5%, 1.9%, 2%, 2.5%, 2.9%, 3%, 3.5%, 3.85%, 4%, 4.5%, 5%, 5.5%, 5.7%, and 6%.
[0030] In one embodiment, the graft polymerization of polybutadiene latex, styrene, and acrylonitrile can be achieved by an emulsion polymerization process to prepare ABS rubber powder.
[0031] In one embodiment, the preparation method of ABS rubber powder comprises the following steps:
[0032] Providing a first mixture and heating the first mixture to 45-55° C. (e.g., 48° C., 50° C., 52° C.); the first mixture includes polybutadiene latex, an activator, and a first portion of an initiator;
[0033] Providing a pre-emulsified mixture, the pre-emulsified mixture comprising styrene, acrylonitrile, a molecular weight regulator, remaining initiator, an emulsifier and a conductive nanomaterial;
[0034] adding (e.g., dropping) the pre-emulsified mixture into the first mixture to obtain a second mixture; and
[0035] The second mixture is reacted at 75 to 85° C. (eg, 80° C.) to obtain a third mixture.
[0036] In one embodiment, the pre-emulsified mixture is dripped into the first mixture within 1 to 5 hours, and the dripping time may further be 2 to 4 hours, for example 3 hours.
[0037] In one embodiment of the present invention, conductive nanomaterials are added during the graft polymerization process, thereby encapsulating the nanoparticles in the graft shell layer of the graft latex, thereby improving the electroplating performance and thermal performance of the subsequently prepared ABS resin.
[0038] In one embodiment, the reaction time of the second mixture is 2 to 6 hours, further 3 to 4 hours.
[0039] In one embodiment, a composite latex antioxidant is added to the third mixture at ambient temperature to obtain a grafted latex; the ambient temperature may be 15 to 35° C., such as 20° C., 22° C., 25° C., 28° C., 30° C., 32° C. Further, the grafted latex is coagulated and dried to obtain ABS rubber powder.
[0040] In one embodiment, the preparation method of ABS rubber powder comprises the following steps:
[0041] (1) adding an activator and a portion of cumene hydroperoxide to 60 parts of polybutadiene latex, and heating the mixture to 50° C. with stirring;
[0042] (2) adding styrene, acrylonitrile, a molecular weight regulator, remaining cumene hydroperoxide, an emulsifier and a conductive nanomaterial into an emulsification bottle and performing pre-emulsification;
[0043] (3) continuously dropping the mixture in the emulsification bottle into the polybutadiene latex in step (1) within a specified time;
[0044] (4) After the dropwise addition is completed, the temperature is raised to 80° C. and the reaction is continued for a period of time. After the reaction is completed, the temperature is lowered to room temperature and a composite latex antioxidant is added thereto to obtain a grafted latex;
[0045] (5) The obtained grafted latex is subjected to coagulation and fluidized drying to obtain ABS rubber powder.
[0046] One embodiment of the present invention provides an ABS rubber powder, which is prepared by the above composition or the above preparation method.
[0047] An embodiment of the present invention provides an ABS rubber powder, comprising a core layer and a shell layer, wherein the shell layer contains a conductive nano material. Further, the types of the conductive nano material are subject to the aforementioned definition.
[0048] One embodiment of the present invention provides a composition for preparing ABS resin, comprising the above-mentioned ABS rubber powder and styrene-acrylonitrile copolymer (SAN resin).
[0049] In one embodiment, the composition for preparing ABS resin includes 20 to 40 parts by mass (eg, 25 parts by mass, 30 parts by mass) of ABS rubber powder and 60 to 80 parts by mass (eg, 70 parts by mass, 75 parts by mass) of styrene-acrylonitrile copolymer.
[0050] In one embodiment, the composition for preparing ABS resin includes ABS rubber powder, styrene-acrylonitrile copolymer and auxiliary agent, and the auxiliary agent may include lubricant and / or antioxidant. Further, the composition for preparing ABS resin includes 20-40 parts by mass of ABS rubber powder, 60-80 parts by mass of styrene-acrylonitrile copolymer, 1 part by mass of lubricant and 1.2 parts by mass of antioxidant.
[0051] In one embodiment, the mass content of acrylonitrile in the styrene-acrylonitrile copolymer may be 20-36%, further may be 24-32%, for example, 25%, 28%, 30%.
[0052] In one embodiment, the weight average molecular weight of the styrene-acrylonitrile copolymer is 80,000 to 200,000 g / mol, for example, 100,000 g / mol, 120,000 g / mol, 150,000 g / mol, or 180,000 g / mol.
[0053] In one embodiment, the ABS resin can be prepared by co-blending and extruding the components of the composition for preparing the ABS resin. Further, a twin-screw extruder can be used for co-blending and extrusion.
[0054] In one embodiment, the preparation method of ABS resin comprises the following steps:
[0055] Prepare grafted latex according to the above method;
[0056] A magnesium sulfate solution and deionized water are added to the reaction kettle and the temperature is raised. Under stirring conditions, the grafted latex is slowly dripped into the reaction kettle. After the dripping is completed, stirring is continued to obtain a coagulated latex; the obtained coagulated latex is filtered using a stainless steel filter cloth to obtain a wet rubber powder, which is then dried in a fluidized bed to obtain an ABS rubber powder; and
[0057] A twin-screw extruder is used to mix and extrude ABS rubber powder, SAN resin and additives in a certain proportion to obtain ABS resin pellets.
[0058] One embodiment of the present invention provides an electroplated product, including a substrate layer and an electroplated layer, wherein the substrate layer includes an ABS resin prepared from the above composition.
[0059] In one embodiment, the electroplating layer is a metal layer, for example, may include three metals: copper, nickel, and chromium.
[0060] In one embodiment, the plating bonding strength between the substrate layer and the electroplating layer of the electroplated article is 2 to 16 N / cm, for example, 5 N / cm, 6.6 N / cm, 7 N / cm, 7.1 N / cm, 7.5 N / cm, 8 N / cm, 8.1 N / cm, 8.5 N / cm, 10 N / cm, 12 N / cm, 12.6 N / cm, 13 N / cm, 13.6 N / cm, 14 N / cm, 15 N / cm, and 15.8 N / cm, as measured according to ASTM B533.
[0061] The ABS resin according to one embodiment of the present invention has a lower linear expansion coefficient and a higher electroplating bonding force, and is suitable for electroplating.
[0062] The ABS resin of one embodiment of the present invention embeds the conductive nanomaterial in the latex grafted shell layer, so that the conductive nanomaterial is dispersed more evenly and the product performance is improved more stably.
[0063] The ABS resin of one embodiment of the present invention includes a conductive nanomaterial embedded in a grafted shell layer of latex. When the polybutadiene rubber on the surface of the resin is etched by a roughening liquid, these nanomaterial particles can be evenly exposed on the surface of the anchor point, which is more conducive to chemical plating and electroplating, thereby effectively improving the bonding force between the metal plating layer and the resin substrate.
[0064] In one embodiment of the present invention, a conductive nanomaterial (e.g., conductive nanoparticles) is introduced into a graft shell layer of an acrylonitrile-butadiene-styrene graft polymer during the graft polymerization process for preparing ABS rubber powder; the conductive nanoparticles embedded in the graft layer not only have excellent adhesion but also are very evenly dispersed. On the one hand, the conductive nanoparticles can be evenly dispersed in the anchor points formed after the prepared ABS resin is coarsened, which is beneficial to chemical plating on the resin surface, thereby greatly improving the electroplating bonding force of the ABS resin; on the other hand, the conductive nanomaterial used has excellent heat resistance and low linear expansion coefficient, which can further improve the heat resistance of the ABS resin and reduce its linear expansion coefficient, greatly reducing cracking, bulging, and other phenomena that occur in electroplated plastic parts in high-temperature application scenarios.
[0065] The following is a further description of the preparation method and application of ABS resin according to an embodiment of the present invention in conjunction with the accompanying drawings and specific examples. Part of the raw materials used are as follows:
[0066] Polybutadiene latex: produced by Wanhua Chemical, solid content of 50wt%, particle size of 200-400nm; the amount of polybutadiene latex used in each embodiment and comparative example has been converted into solid content;
[0067] Conductive particles: single-layer graphene;
[0068] SAN resin: Chimei AS resin, brand: PN-128;
[0069] Lubricant: Commercially available EBS;
[0070] Composite emulsion antioxidant: commercially available FK301;
[0071] Solid antioxidant: commercially available TG-1076;
[0072] Potassium oleate: 50%, industrial grade, Qingdao Ruinuo Chemical Co., Ltd.;
[0073] Cumene hydroperoxide: 500 g, 80%, purchased from Acros;
[0074] Tert-dodecyl mercaptan: 200 g, AR, purchased from Isu Chemical, Korea.
[0075] Example 1
[0076] (1) adding 0.002 parts by weight of ferrous sulfate as an activator and 0.1 parts by weight of cumene hydroperoxide to 60 parts by weight of polybutadiene latex, and heating the mixture to 50° C. with stirring;
[0077] (2) adding 30 parts by mass of styrene, 10 parts by mass of acrylonitrile, 0.2 parts by mass of tert-dodecyl mercaptan, 0.1 parts by mass of cumene hydroperoxide, 0.3 parts by mass of potassium oleate and 1 part by mass of monolayer graphene into an emulsification bottle and performing pre-emulsification;
[0078] (3) continuously adding the mixture in the emulsification bottle to the polybutadiene latex in step (1) within 2 hours;
[0079] (4) After the addition was completed, the temperature was raised to 80° C. and the reaction was continued for 3 h. After the reaction was completed and the temperature was lowered to room temperature, a composite latex antioxidant FK301 was added to the system to obtain a grafted latex;
[0080] (5) adding magnesium sulfate solution and deionized water to a reaction kettle and heating the kettle to 70° C., slowly dropping the grafted latex into the reaction kettle under stirring, and continuing to stir after the dropping is completed to obtain a coagulated latex; filtering the obtained coagulated latex with a stainless steel filter cloth to obtain a wet rubber powder, and then drying it in a fluidized bed to obtain an ABS rubber powder;
[0081] (6) 25 parts by weight of ABS rubber powder, 75 parts by weight of SAN resin, 1 part by weight of lubricant EBS, and 1.2 parts by weight of solid antioxidant TG-1076 were mixed and extruded using a twin-screw extruder to obtain ABS resin pellets.
[0082] The ABS resins of Examples 1-1 to 5 and Comparative Examples 1 to 2 were prepared using substantially the same process and raw materials as in Example 1, except that: the amounts of polybutadiene latex, styrene and acrylonitrile were different, the types and amounts of conductive nanomaterials were different, the amounts of ABS rubber powder and SAN resin were different, and no conductive nanomaterials were added in the preparation of the ABS rubber powders of Comparative Examples 1 and 2. For details, see Table 1.
[0083] Comparative Example 3
[0084] (1) adding 0.002 parts by weight of ferrous sulfate as an activator and 0.1 parts by weight of cumene hydroperoxide to 60 parts by weight of polybutadiene latex, and heating the mixture to 65° C. with stirring;
[0085] (2) adding 30 parts by mass of styrene, 10 parts by mass of acrylonitrile, 0.2 parts by mass of tert-dodecyl mercaptan, 0.1 parts by mass of cumene hydroperoxide and 0.3 parts by mass of potassium oleate into an emulsification bottle and performing pre-emulsification;
[0086] (3) continuously adding the mixture in the emulsification bottle to the polybutadiene latex in step (1) within 2 hours;
[0087] (4) After the addition was completed, the temperature was raised to 80° C. and the reaction was continued for 3 h. After the reaction was completed and the temperature was lowered to room temperature, a composite latex antioxidant FK301 was added to the system to obtain a grafted latex;
[0088] (5) adding magnesium sulfate solution and deionized water to a reaction kettle and heating the kettle to 70° C., slowly dropping the grafted latex into the reaction kettle under stirring, and continuing to stir after the dropping is completed to obtain a coagulated latex; filtering the obtained coagulated latex with a stainless steel filter cloth to obtain a wet rubber powder, and then drying it in a fluidized bed to obtain an ABS rubber powder;
[0089] (6) 25 parts by mass of ABS rubber powder, 75 parts by mass of SAN resin, 1 part by mass of lubricant EBS, 1.2 parts by mass of solid antioxidant TG-1076 and 4 parts by mass of monolayer graphene were mixed and extruded using a twin-screw extruder to obtain ABS resin pellets.
[0090] The ABS resins of Comparative Examples 3-1 to 3-2 were prepared using substantially the same process and raw materials as those of Comparative Example 3, with the only difference being that the types of conductive nanomaterials were different, as shown in Table 1.
[0091] Table 1
[0092]
[0093]
[0094] The ABS resins prepared in the embodiments and comparative examples were injection molded into corresponding test specimens according to the test method in Table 2 to characterize the mechanical and thermal properties of the resins. The results are shown in Table 3.
[0095] Table 2 Physical performance test standards
[0096] Physical properties Test Method Melt index (220℃,10kg) ASTM D1238 Izod impact strength (23℃, 3.2mm) ISO 180 Vicat softening point (50N, 50℃ / h) ISO 306 Linear expansion coefficient ISO 11359
[0097] Electroplating bonding test
[0098] The ABS resin obtained in each embodiment and comparative example was injection molded into a 150mm*100mm*100mm plastic sample at 220°C, and electroplated under the standard electroplating process of the electroplating plant. The electroplated layer includes three metals: copper, nickel, and chromium, wherein the thickness of the copper layer is 25μm, the thickness of the semi-bright nickel layer is ≥7.5μm, the thickness of the bright nickel layer is ≥7.5μm, the thickness of the microporous nickel layer is ≥1.5μm, and the thickness of the microporous chromium layer is 0.3-0.5μm. The obtained electroplated ABS sample was cut into 100mm*10mm strips, and the electroplating bonding strength test was carried out according to the ASTMB533 plastic electroplating parts peeling strength test standard. The electroplating bonding strength readings were uniformly taken as the average value of the 10-20mm interval. The results are shown in Table 3.
[0099] Table 3 Performance test results of ABS resin in various embodiments and comparative examples
[0100]
[0101]
[0102] According to the description of the above-mentioned embodiments, the difference between Example 1 and Example 1-1 and Comparative Example 1 is that no conductive nanomaterials are added in the preparation of the ABS rubber powder of Comparative Example 1; the difference between Examples 1-2 to Example 3 and Comparative Example 2 is that no conductive nanomaterials are added in the preparation of the ABS rubber powder of Comparative Example 2. The results in Table 3 show that on the basis of basically unchanged mechanical properties, compared with the ABS resin of Comparative Example 1, the ABS resins of Examples 1 and Example 1-1 have lower linear expansion coefficients and higher electroplating bonding strength. Similarly, compared with the ABS resin of Comparative Example 2, the ABS resins of Examples 1-2 to Example 3 have lower linear expansion coefficients and higher electroplating bonding strength. Therefore, by adding conductive nanomaterials in the preparation of ABS rubber powder, the linear expansion coefficient of the obtained ABS resin can be reduced and its electroplating bonding strength can be improved.
[0103] Further, the difference between Example 1 and Example 1-1 and between Example 1-2 and Examples 1-3 to 1-5 is that the amount of conductive nanomaterials is different. According to the results in Table 3, although the use of conductive nanomaterials can reduce the linear expansion coefficient of ABS resin, as the amount of conductive nanomaterials increases, the electroplating bonding force shows a trend of first increasing and then decreasing, and the melt index and impact resistance also decrease accordingly. Therefore, in the composition for preparing ABS rubber powder, when the amount of polybutadiene latex is 60 parts by mass, the amount of conductive nanomaterials is preferably 0.5 to 6 parts by mass, and accordingly, the conductive nanomaterials preferably account for 0.49 to 5.7% of the total mass of the ABS rubber powder.
[0104] Further, the difference between Examples 1-4, Example 2 and Example 3 is that the types of conductive nanomaterials used are different. According to the results in Table 3, the addition of these three conductive nanomaterials can reduce the linear expansion coefficient of ABS resin and improve the electroplating bonding force. The conductive nanomaterial is preferably graphene and carbon nanotubes, more preferably graphene.
[0105] Furthermore, the difference between Examples 1-4 and Comparative Example 3, Example 2 and Comparative Example 3-1, and Example 3 and Comparative Example 3-2 is that the conductive nanomaterials are mixed in different ways. The conductive nanomaterials are added in the graft polymerization process in each example, and the conductive nanomaterials are added in the same mass fraction in the mixing stage in the comparative example. According to the results in Table 3, under both mixing methods, the conductive nanomaterials can improve the electroplating bonding force of ABS resin and reduce the linear expansion coefficient. However, the improvement effect of adding conductive nanomaterials in the graft polymerization process is more significant. It can be observed through TEM electron microscopy that Figure 2 (TEM image of grafted latex in comparative example 3) The grafted shell does not contain conductive particles. Figure 3 There are black conductive particles in the grafted shell layer of (TEM images of grafted latex of Examples 1-4), which indicates that the conductive nanomaterials added during the graft polymerization process can be wrapped in the shell layer formed by the styrene-acrylonitrile graft copolymer, thereby greatly improving the uniformity of its dispersion on the ABS resin surface.
[0106] Unless otherwise defined, the terms used in the present invention have the meanings commonly understood by those skilled in the art.
[0107] The embodiments described in the present invention are for illustrative purposes only and are not intended to limit the scope of protection of the present invention. Those skilled in the art may make various other substitutions, changes and improvements within the scope of the present invention. Therefore, the present invention is not limited to the above embodiments, but is only limited by the claims.
Claims
1. A composition for preparing ABS rubber powder, comprising polybutadiene latex, styrene, acrylonitrile and additives, wherein the additives include conductive nanomaterials.
2. The composition according to claim 1, comprising 40 to 80 parts by mass of the polybutadiene latex, 20 to 40 parts by mass of the styrene, 5 to 20 parts by mass of the acrylonitrile and 0.2 to 6 parts by mass of the conductive nanomaterial, wherein: The amount of the polybutadiene latex is calculated based on its solid content; and / or, The particle size of the polybutadiene latex is 100 to 800 nm, further 200 to 400 nm; and / or, The composition includes 0.1 to 8.5 wt % of the conductive nanomaterial.
3. The composition according to claim 1, comprising a reaction aid, wherein the reaction aid comprises one or more of an activator, an initiator, and a molecular weight regulator; and / or, The additives include emulsifiers and / or antioxidants; and / or, The conductive nanomaterial includes one or more of graphene, nano-copper, nano-nickel, and carbon nanotube.
4. The composition according to claim 3, comprising 40 to 80 parts by mass of the polybutadiene latex, 20 to 40 parts by mass of the styrene, 5 to 20 parts by mass of the acrylonitrile, 0.001 to 0.004 parts by mass of the activator, 0.002 to 0.2 parts by mass of the initiator, 0.1 to 0.6 parts by mass of the molecular weight regulator, 0.1 to 0.6 parts by mass of the emulsifier, 0.05 to 0.3 parts by mass of the antioxidant and 0.5 to 5 parts by mass of the conductive nanomaterial; and / or, The activator is ferrous salt, the initiator is peroxide, the molecular weight regulator is a thiol compound, the emulsifier is fatty acid soap, and the antioxidant is a composite emulsion antioxidant.
5. A method for preparing ABS rubber powder, comprising preparing ABS rubber powder by using the composition according to any one of claims 1 to 4; wherein: The ABS rubber powder comprises a core layer and a shell layer, and the shell layer contains the conductive nanomaterial.
6. The preparation method according to claim 5, comprising the steps of: Providing a first mixture, and heating the first mixture to 45-55° C.; the first mixture comprises polybutadiene latex, an activator and a first portion of an initiator; Providing a pre-emulsified mixture, the pre-emulsified mixture comprising styrene, acrylonitrile, a molecular weight regulator, remaining initiator, an emulsifier and a conductive nanomaterial; adding the pre-emulsified mixture to the first mixture to obtain a second mixture; and The second mixture is reacted at 75-85°C.
7. An ABS rubber powder, comprising a core layer and a shell layer, wherein the shell layer contains conductive nanomaterials.
8. A composition for preparing ABS resin, comprising the ABS rubber powder prepared by the preparation method according to claim 5 or 6 or the ABS rubber powder according to claim 7 and a styrene-acrylonitrile copolymer.
9. The composition according to claim 8, comprising an auxiliary agent, wherein the auxiliary agent comprises a lubricant and / or an antioxidant; and / or, The mass content of acrylonitrile in the styrene-acrylonitrile copolymer is 20 to 36%; and / or, The weight average molecular weight of the styrene-acrylonitrile copolymer is 80,000 to 200,000 g / mol; and / or, The composition for preparing ABS resin comprises 20 to 40 parts by mass of the ABS rubber powder and 60 to 80 parts by mass of the styrene-acrylonitrile copolymer.
10. An electroplated product comprising a substrate layer and an electroplated layer, wherein the substrate layer comprises an ABS resin prepared from the composition according to claim 8 or 9.
Citation Information
Patent Citations
Method for in-situ modification of ABS (acrylonitrile-butadiene-styrene) resin by graphene
CN104194248A
Heat-resisting electroplating ABS resin excellent in high and low temperature cycling resistance and preparation method thereof
CN106188928A
ABS resin composition and preparation method thereof
CN110684295A
Eco-friendly and excellent in electro-plating properties of thermoplastic resin composition
TW201623420A
Environment-friendly thermoplastic resin composition having excellent plating properties
WO2016108461A1